2010
DOI: 10.1111/j.1750-3841.2010.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Campylobacter jejuni Isolated from Pasture Flock Poultry

Abstract: Campylobacter jejuni is a leading cause of foodborne illness with poultry and poultry products being leading sources of infection. Free-range and pasture flock chickens are becoming more popular; however, there is an inherent biosecurity risk that can increase the prevalence of foodborne pathogens in these flocks. This study aimed to determine sources and characterize C. jejuni isolated from pasture flocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 50 publications
3
23
2
3
Order By: Relevance
“…The pldA and ciaB genes have been detected from C. jejuni poultry isolates at the frequencies of 63.6 and 67.3%, respectively (Melo et al, 2013). Hanning et al (2010) reported relatively low detection frequencies of ciaB (40%) and pldA (56%) in C. jejuni isolates from poultry carcasses. The virB11 gene is located in the virulence plasmid pVir, which is often detected in C. jejuni strains that cause bloody diarrhea (Bacon et al, 2002; Tracz et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…The pldA and ciaB genes have been detected from C. jejuni poultry isolates at the frequencies of 63.6 and 67.3%, respectively (Melo et al, 2013). Hanning et al (2010) reported relatively low detection frequencies of ciaB (40%) and pldA (56%) in C. jejuni isolates from poultry carcasses. The virB11 gene is located in the virulence plasmid pVir, which is often detected in C. jejuni strains that cause bloody diarrhea (Bacon et al, 2002; Tracz et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…This gene has also been detected in 28% of the C. jejuni strains isolated from free-range broiler flocks (Hanning et al, 2010) and with a low prevalence for C. coli from various origins (Wieczorek and Osek, 2010, 2013; Acik et al, 2013). The low frequency of these isolates did not allow us to conclude that their presence in organic farms is related to the management of this type of production system.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence, only few such investigations have been performed, and it is difficult to judge how representative these studies are for other flocks or other slaughterhouses (Hanning et al . ; Kudirkiene et al . ).…”
Section: Introductionmentioning
confidence: 99%